MENGONTROL EMOSI PADA ANAK PRA SEKOLAH OLEH ORANG TUA DI TK NEGERI PEMBINA PARE KEDIRI (Pengabdian Kepada Masyarakat) - Ariani Sulistyorini; Widyasih Sunaringtyas; Nove Lestari (STIKES dan AKZI Karya Husada Kediri, 2023)
The problem that children often face is about controlling their emotions. Controlling children's emotions is not an easy thing to do, including adults. For this reason, special tricks are needed on how to teach children to manage their emotions in the best way so that children's emotions can be channeled correctly and healthily. The purpose of this community service is to educate parents on how to control emotions in pre-school children. The method used in community service is education using lecture, question and answer and role play methods. The implementation time is December 22 and 24 2022 at the Pembina Pare State Kindergarten, Kediri with 65 parents participating. After we provided education to the teachers and parents of students at Pembina Pare Public Kindergarten, Kediri Regency, the knowledge and abilities of 20 parents (30%) were good, 35 parents (55%) had enough and 10 parents (15%) were still lack of emotional control in preschool children. Some ways that can be used to control emotions are teaching children how to calm down, how to express feelings, teach them not to harbor anger, empathize with children, set a good example, set boundaries, teach them to stay away from emotional causes, avoid punishing children, talk about emotions and feelings, teach how to recognize other people's feelings, how to solve problems, learn to listen, hug when children are angry, don't fight in front of children and talk when emotions subside. Controlling emotions is very important so that emotions can be controlled properly as well as teaching children how to identify signs of anger and find the best way to think calmly while being productive in action. If these emotions can be controlled properly, then these bad habits will also be very helpful so that children can avoid angry outbursts that not only hurt the people around them but also hurt the children themselves.